2018
DOI: 10.1177/1350650117753530
|View full text |Cite
|
Sign up to set email alerts
|

Finite element method analysis of hydrostatic thrust pad bearings operating with electrically conducting lubricant

Abstract: A theoretical investigation has been carried out to explore the use of electrically conducting fluids as lubricants in circular and elliptical hydrostatic thrust pad bearings subjected to transverse magnetic field. Flow of electrically conducting fluid in the presence of external transverse magnetic field is represented by the addition of Lorentz force in Navier-Stokes equation. A MATLAB source code based on finite element formulation of the modified Reynolds equation is developed for obtaining static and dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Figure 1c) are considered in the present investigation. Based on the available literature [26][27][28][29][30][31][32][33][34][35][36][37], two values of Hartmann number have been chosen to represent Newtonian lubricant (H = 0) and electrically conducting lubricant (H = 3) in numerical simulations. Performance has been evaluated in terms of non-dimensional physical quantities, namely fluid film pressure profile, loadcarrying capacity, lubricant flow rate, frictional power loss, fluid film stiffness and damping coefficients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1c) are considered in the present investigation. Based on the available literature [26][27][28][29][30][31][32][33][34][35][36][37], two values of Hartmann number have been chosen to represent Newtonian lubricant (H = 0) and electrically conducting lubricant (H = 3) in numerical simulations. Performance has been evaluated in terms of non-dimensional physical quantities, namely fluid film pressure profile, loadcarrying capacity, lubricant flow rate, frictional power loss, fluid film stiffness and damping coefficients.…”
Section: Resultsmentioning
confidence: 99%
“…The above-mentioned studies predicted a substantial enhancement in external load bearing capacity and time of approach (of squeeze film) with the magnetohydrodynamic lubrication in their respective bearings. Recently, Kumar and Sharma [34][35][36] numerically simulated the hydrostatic thrust bearings, considering influence of pocket shape and compensating element, operating with magneto-hydrostatic lubrication. The authors reported that the steady-state and dynamic characteristics of hydrostatic bearings can be suitably managed by manufacturing non-conventional recess shapes in the thrust pad.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The geometric/operating parameters and electrically conducting lubricant rheological properties shown in Table 2, have been taken from the available literature. 1,2,4,10,14,22,[37][38][39][40][41][42][43][44] Based on the literatures, the lubricant properties and the geometric/operating parameters have been judiciously selected.…”
Section: Resultsmentioning
confidence: 99%
“…Electrically conducting Lubricant properties and bearing operating, geometric parameters. 1,2,4,10,14,22,[37][38][39][40][41][42][43][44] Bearing depict the surface irregularities and ECL in a magnetic field enhances the value of " h min . The surface irregularities offer more divergent and convergent regions at the bearing surface.…”
Section: Minimum Fluid Film Thickness "mentioning
confidence: 99%